2005
DOI: 10.1086/431950
|View full text |Cite
|
Sign up to set email alerts
|

All Coronal Loops Are the Same: Evidence to the Contrary

Abstract: The 1998 April 20 spectral line data from the Coronal Diagnostic Spectrometer on the Solar and Heliospheric Observatory show a coronal loop on the solar limb. Our original analysis of these data showed that the plasma was multithermal, both along the length of the loop and along the line of sight. However, more recent results by other authors indicate that background subtraction might change these conclusions, so we consider the effect of background subtraction on our analysis. We show emission measure (EM) lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Most of these previous models assume monolithic equilibrium configurations with uniform internal density in the direction transverse to field lines, which is an over-simplification of the real physical conditions in coronal loops. For instance, high-resolution observations suggest the existence of sub-resolution transverse structuring, not accessible to direct observation with our current capabilities (Schmelz et al 2005). This view has been challenged in some works (Aschwanden & Nightingale 2005;Aschwanden 2005), although it is supported in some others (e.g.…”
Section: Introductionmentioning
confidence: 86%
“…Most of these previous models assume monolithic equilibrium configurations with uniform internal density in the direction transverse to field lines, which is an over-simplification of the real physical conditions in coronal loops. For instance, high-resolution observations suggest the existence of sub-resolution transverse structuring, not accessible to direct observation with our current capabilities (Schmelz et al 2005). This view has been challenged in some works (Aschwanden & Nightingale 2005;Aschwanden 2005), although it is supported in some others (e.g.…”
Section: Introductionmentioning
confidence: 86%
“…In the least, contamination from diffuse background and/or foreground emission is present, or the plasma is multithermal (e.g., Schmelz et al 2005;Schmelz & Martens 2006;Cirtain et al 2007;Schmelz et al 2007aSchmelz et al , 2008Aschwanden et al 2008;Schmelz et al 2009a;Terzo & Reale 2010;O'Dwyer et al 2010), or there is a contribution from low-intensity high-temperature component (e.g. Reale et al 2009a,b;Schmelz et al 2009b,c).…”
Section: Temperature Diagnostic Using Cifrmentioning
confidence: 99%
“…Moreover it has also been suggested that the coronal magnetic loops are in fact collections of very thin magnetic ropes bundled together (e.g. Martens et al 2002;Schmelz et al 2003Schmelz et al , 2005Aschwanden 2005;Aschwanden & Nightingale 2005). It is therefore important to understand how the interaction of these neighbouring loops affects the oscillations and damping of coronal loops.…”
Section: Introductionmentioning
confidence: 99%